Exploring the role of the nutrition nurse specialist in an intestinal failure tertiary referral centre. (7th April 2022) - Malhi, Hardip; Dera, Merceline; Fletcher, Jane
Abstract : The role of the nutrition nurse specialist (NNS) is diverse and is usually integral to a wider, multidisciplinary nutrition support team (NST). Practice frameworks have been developed to identify competencies within the NNS role. A mind-mapping technique was used with the NNS team and the wider NST to explore the role of the NNS in the authors' intestinal failure tertiary referral centre. The results of this were further compared with the published competency frameworks. The mind maps from the NNS team and NST demonstrated commonality. It was encouraging to see that colleagues seem to have a similar understanding of the NNS role and contribution to the wider service. Published competency frameworks did not entirely reflect the expanded scope of practice that is undertaken within this particular team. It is important for clinical nurse specialist teams to evaluate their role and service provision and to compare this against published competency frameworks.